Real-World Cataract Surgery Complications and Secondary Interventions Incidence Rates: An Analysis of US Medicare Claims Database - Daniel Terveen; John Berdahl; Mukesh Dhariwal; Qian Meng (Journal of Ophthalmology, 2022)
Purpose. To characterize cataract patients and postoperative outcomes in the Medicare fee-for-service (FFS) population. Design. A retrospective observational cohort study. Methods. Medicare fee-for-service (A&B) databases were queried from October 2015 to December 2017. Patients with procedural claims using CPT codes (66982 or 66984) and with 1–12 months of postcataract follow-up data were included in the analysis. Results. 133,896 records of 82,246 CMS FFS claims were included in the analysis. The average patient age was 73.8, and 58.2% were females. The cataract surgery setting was ASC (71.3%) followed by HOPD (27.6%). The median time between first and second surgery was 15 days. The most common comorbidities included diabetes (28.6%), glaucoma (22.1%), and macular degeneration (21.7%). Posterior capsule rupture occurred in 0.2% of cases. The <6 months cumulative incidence of most common secondary surgical interventions was 4.7%, 0.2%, and 0.2% for Nd:YAG capsulotomy, IOL exchange, and IOL repositioning, respectively. Discussion. Real-world complication rates of cataract surgery may help reduce postcataract complications and procedure burden. Synopsis for Table of Contents. This study focused on a sample of the US Medicare beneficiary cataract population and describes its demographic characteristics and reports the cumulative incidence of common postcataract surgery complications and secondary surgical interventions (SSI).